A comparative study of loneliness from psychological well being as predictor of mental health students living in dormitories: A cross cultural study - Nadhilah, Amalia; Jati, Sri Nugroho; Visyastuti, Vidyastuti (Jurnal Psikologi Tabularasa, 2024)
ABSTRACTThis cross-cultural study looked at levels of loneliness that reviewed psychological well-being as a predictor of mental health in students in Indonesia and Malaysia living at the Asrama. Loneliness Statistics states that 43% of 17-25-year-olds feel loneliness and psychological well-being as one of the predictive factors of the level of loneliness. Interviews showed that students felt lonely due to differences and changes in the environment. Feeling alone, hard to adapt, and incapable of growing. A total of 235 Indonesian and Malaysian students live in dorms. Instrument scale with loneliness and psychological well-being. Purposive sampling technique. Independent sample t-test for comparative data analysis of lonely Indonesian and Malaysian students living in dorms. Regression test to see impact of psychological well-being on loneliness. While Malaysian and Indonesian students reported comparable levels of loneliness, the study also discovered that psychological well-being had an impact on loneliness. The implications of this research are that by understanding the importance of improving understanding and implementing psychological well-being effectively, students can overcome feelings, situations and conditions that cause loneliness and have a healthy mentality.ABSTRACTPenelitian cross-cultural ini untuk melihat tingkat kesepian yang ditinjau kesejahteraan psikologis sebagai prediktor kesehatan mental pada mahasiswa di Indonesia dan Malaysia yang tinggal di Asrama. Loneliness Statistics menyatakan bahwa 43% yang berusia 17-25 tahun merasa kesepian dan kesejahteraan psikologis menjadi salah satu faktor yang memprediksi tingkat kesepian. Wawancara awal menunjukkan mahasiswa merasa kesepian akibat adanya perbedaan dan perubahan lingkungan. Perasaan terasingkan, sulit beradaptasi, tidak percaya diri dan tidak mampu mengembangkan diri. Sebanyak 235 mahasiswa Indonesia dan Malaysia tinggal di asrama dilibatkan. Instrumen dengan skala kesepian dan kesejahteraan psikologis. Teknik pengambilan dengan purposive sampling. Metode independent sample t-test untuk analisis data perbandingan kesepian mahasiswa Indonesia dan Malaysia yang tinggal di asrama. Serta, uji regresi untuk melihat pengaruh kesejahteraan psikologis terhadap kesepian. Hasil penelitian menemukan adanya persamaan pada tingkat kesepian mahasiswa Malaysia maupun Indonesia namun ditemukan kesejahteraan psikologis berpengaruh pada kesepian. Implikasi dari penelitian ini menghasilkan bahwa memahami pentingnya meningkatkan pemahaman dan penerapan kesejahteraan psikologis secara efektif, sehingga mahasiswa bisa mengatasi perasaan, situasi dan kondisi yang menyebabkan kesepian serta memiliki mental yang sehat.